Caspase-2 mediates a Brucella abortus RB51-induced hybrid cell death having features of apoptosis and pyroptosis - Bronner, Denise N.; O'Riordan, Mary; He, Yongqun "Oliver" (Frontiers in Cellular and Infection Microbiology, 2013)
Programmed cell death (PCD) can play a crucial role in tuning the immune response to microbial infection. Although PCD can occur in different forms, all are mediated by a family of proteases called caspases. Caspase-2 is the most conserved caspase, however, its function in cell death is ill-defined. Previously we demonstrated that live attenuated cattle vaccine strain Brucella abortus RB51 induces caspase-2-mediated and caspase-1-independent PCD of infected macrophages. We also discovered that rough attenuated B. suis strain VTRS1 induces a caspase-2-mediated and caspase-1-independent proinflammatory cell death in infected macrophages, which was tentatively coined “caspase-2-mediated pyroptosis”. However, the mechanism of caspase-2-mediated cell death pathway remained unclear. In this study, we found that caspase-2 mediated proinflammatory cell death of RB51-infected macrophages and regulated many genes in different PCD pathways. We show that the activation of proapoptotic caspases-3 and -8 was dependent upon caspase-2. Caspase-2 regulated mitochondrial cytochrome c release and TNFα production, both of which are known to activate caspase-3 and caspase-8, respectively. In addition to TNFα, RB51-induced caspase-1 and IL-1β production was also driven by caspase-2-mediated mitochondrial dysfunction. Interestingly, pore formation, a phenomenon commonly associated with caspase-1-mediated pyroptosis, occurred; however, unlike its role in S. typhimurium-induced pyroptosis, pore formation did not contribute to RB51-induced proinflammatory cell death. Our data suggest that caspase-2 acts as an initiator caspase that mediates a novel RB51-induced hybrid cell death that simulates but differs from typical non-proinflammatory apoptosis and caspase-1-mediated proinflammatory pyroptosis. The initiator role of the caspase-2-mediated cell death was also conserved in cellular stress-induced cell death of macrophages treated with etoposide, naphthalene, or anti-Fas. Caspase-2 also regulated caspase-3 and -8 activation, as well as cell death in macrophages treated with each of the three reagents. Taken together, our data has demonstrated that caspase-2 can play an important role in mediating a proinflammatory response and a hybrid cell death that demonstrates features of both apoptosis and pyroptosis.